2020
DOI: 10.3390/cancers12082263
|View full text |Cite
|
Sign up to set email alerts
|

Uptake Transporters of the SLC21, SLC22A, and SLC15A Families in Anticancer Therapy—Modulators of Cellular Entry or Pharmacokinetics?

Abstract: Solute carrier transporters comprise a large family of uptake transporters involved in the transmembrane transport of a wide array of endogenous substrates such as hormones, nutrients, and metabolites as well as of clinically important drugs. Several cancer therapeutics, ranging from chemotherapeutics such as topoisomerase inhibitors, DNA-intercalating drugs, and microtubule binders to targeted therapeutics such as tyrosine kinase inhibitors are substrates of solute carrier (SLC) transporters. Given that SLC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 224 publications
(298 reference statements)
0
17
0
Order By: Relevance
“…This indicates that C1 may exhibit high sensitivity to anti-androgenic therapy. With a high expression of immune checkpoints and significant features of immune cell infiltration, C2 tumors may benefit more from immune-targeted therapy, whereas C3, with an active status of specific drug metabolism pathways, may facilitate the development of tolerance to traditional chemotherapy (65). In the drug sensitivity analysis of the risk model, our study suggests that patients with low-risk scores may benefit more from anti-PD-1 treatment, and this is consistent with C2 being more suitable for immune target therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that C1 may exhibit high sensitivity to anti-androgenic therapy. With a high expression of immune checkpoints and significant features of immune cell infiltration, C2 tumors may benefit more from immune-targeted therapy, whereas C3, with an active status of specific drug metabolism pathways, may facilitate the development of tolerance to traditional chemotherapy (65). In the drug sensitivity analysis of the risk model, our study suggests that patients with low-risk scores may benefit more from anti-PD-1 treatment, and this is consistent with C2 being more suitable for immune target therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of chemotherapy is also dependent on the intracellular accumulation of anticancer drugs. Cellular uptake of anticancer drugs is mediated by facilitated transport systems via solute carrier (SLC) transporters, suggesting that the expression of SLC transporters may help to predict the response to chemotherapy [ 15 18 ]. The organic cation transporters (OCTs) of the SLC22A family consist of three isoforms, OCT1, OCT2, and OCT3, which mediate the uptake transport of various organic cations including endogenous compounds, xenobiotics, and anticancer drugs [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cellular uptake of anticancer drugs is mediated by facilitated transport systems via solute carrier (SLC) transporters, suggesting that the expression of SLC transporters may help to predict the response to chemotherapy [ 15 18 ]. The organic cation transporters (OCTs) of the SLC22A family consist of three isoforms, OCT1, OCT2, and OCT3, which mediate the uptake transport of various organic cations including endogenous compounds, xenobiotics, and anticancer drugs [ 15 18 ]. An in vitro study demonstrated that transfection of OCT1 increased the accumulation and cytotoxicity of CDDP in human embryonic kidney cells [ 19 ], although another study presented results that were negative for the involvement of OCT1 in the accumulation and cytotoxicity of CDDP [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These transporters utilize an electrochemical or ion gradient to facilitate the exchange of various substances, including endogenous or xenobiotic compounds as well as molecules across the biological membranes, such as sugars, nucleotides, amino acids, nutrients, and drugs 5 , 6 . Recently, a several studies have highlighted that SLC transporters might play a critical role in the initiation, progression, metastasis, and prognosis of human carcinoma 7 , 8 . For instance, Kikuchi et al 9 found that up-regulated SLC37A1 was significantly associated with the venous invasion and liver metastasis of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%